HUBUNGAN KARANTINA KESEHATAN DENGAN WABAH PENYAKIT MENURUT PENAFSIRAN ULAMA DALAM Q.S. 2: 243 - Awaluddin, Raisa Zuhra Salsabila; Murtaza MZ, Ahmad (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2021)
The plague that afflicts humans is terrible and very vicious. Few people who are affected as carriers and who are affected by the outbreak quarantine themselves during the outbreak of the disease. In this regard, Allah has explained in the Qur'an regarding it. The scholars of interpretation in understanding the relationship between quarantine and epidemics can be studied to describe the view of commentators in understanding the relationship between quarantine and disease outbreaks, as well as the relevance of the relationship between quarantine and epidemics in the Qur'an and science to gain a strong understanding in the Qur'an. and science. The relationship between health quarantine and disease outbreaks can be seen in 2 ways: first, through an interpretation which tells about quarantine and epidemics that can become ibrah, and second, through Asbab an-Nuzul Verse in which there is iradah kawniyah which can be understood by Allah commanding us. to self-quarantine. The relevance of the interpretation of the quarantine relationship and the epidemic can be viewed from the purpose of quarantine and quarantine techniques and quarantine history, after observing and spreading the disease, quarantine can be carried out with several types of quarantine.